Hemifacial Spasm Caused by a Huge Tentorial Meningioma - Park, Hun (The Korean Neurosurgical Society, 2009)
A rare case of hemifacial spasm caused by an ipsilateral tentorial meningioma is described. Magnetic resonance imaging showed a huge tumor in the right cerebellar hemisphere, distant to the cerebello-pontine cistern. The facial-vestibulocochlear nerve complex was stretched by the shift of the brainstem and the right cerebello-pontine cistern was effaced. After removing the tumor, the hemifacial spasm resolved completely. We review our case with the pertinent literature regarding the etiological mechanism.